Restricted Sequence Variation in Streptococcus pyogenes Penicillin Binding Proteins - Andrew Hayes (American Society for Microbiology, 2020)
ABSTRACT A recent clinical report has linked Streptococcus pyogenes β-lactam antibiotic resistance to mutation in the penicillin binding protein (PBP) PBP2x. To determine whether this is an isolated case or reflects a broader prevalence of mutations that might confer reduced β-lactam susceptibility, we investigated the relative frequency of PBP sequence variation within a global database of 9,667 S. pyogenes isolates. We found that mutations in S. pyogenes PBPs (PBP2x, PBP1a, PBP1b, and PBP2a) occur infrequently across this global database, with fewer than 3 amino acid changes differing between >99% of the global population. Only 4 of the 9,667 strains contained mutations near transpeptidase active sites of PBP2x or PBP1a. The reported PBP2x T553K substitution was not identified. These findings are in contrast to those of 2,520 S. pneumococcus sequences where PBP mutations are relatively frequent and are often located in key β-lactam binding pockets. These data, combined with the general lack of penicillin resistance reported in S. pyogenes worldwide, suggests that extensive, unknown constraints restrict S. pyogenes PBP sequence plasticity. Our findings imply that while heavy antibiotic pressure may select for mutations in the PBPs, there is currently no evidence of such mutations becoming fixed in the S. pyogenes population or that mutations are being sequentially acquired in the PBPs. IMPORTANCE β-Lactam antibiotics are the first-line therapeutic option for Streptococcus pyogenes infections. Despite the global high prevalence of S. pyogenes infections and widespread use of β-lactams worldwide, reports of resistance to β-lactam antibiotics, such as penicillin, have been incredibly rare. Recently, β-lactam resistance, as defined by clinical breakpoints, was detected in two clinical S. pyogenes isolates with accompanying mutations in the active site of the penicillin binding protein PBP2x, raising concerns that β-lactam resistance will become more widespread. We screened a global database of S. pyogenes genome sequences to investigate the frequency of PBP mutations, identifying that PBP mutations are uncommon relative to those of Streptococcus pneumoniae. These findings support clinical observations that β-lactam resistance is rare in S. pyogenes and suggest that there are considerable constraints on S. pyogenes PBP sequence variation.